2018
DOI: 10.2514/1.c034750
|View full text |Cite
|
Sign up to set email alerts
|

Noise Characterization of a Full-Scale Nose Landing Gear

Abstract: This paper presents experimental results from a nose landing-gear test campaign. A highly detailed model of the nose section of a 90-seat configuration green regional aircraft concept was built and tested in an aeroacoustic open-jet wind tunnel at full scale. All of the landing-gear components, fixtures, and small details and associated structures such as the complete wheel bay, bay doors, and hydraulic dressings were included at full scale. This paper focuses on one element of the testing: that of component n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 36 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…All the spectra are mostly broadband above 600 Hz. The low frequency tonal content of these spectra does not scale, and is the subject of different studies [19,28] which examine the tonal contribution of the wheel bay and LG components in that frequency range. Referring again to Fig.…”
Section: Correlation With Flow Velocitymentioning
confidence: 99%
See 2 more Smart Citations
“…All the spectra are mostly broadband above 600 Hz. The low frequency tonal content of these spectra does not scale, and is the subject of different studies [19,28] which examine the tonal contribution of the wheel bay and LG components in that frequency range. Referring again to Fig.…”
Section: Correlation With Flow Velocitymentioning
confidence: 99%
“…Curle's theory only holds true when the sound sources are compact, i.e., the relationship is true only when the geometric size of the sound source is small when compared to the acoustic wavelength. Guo et al [81] and Bennett et al [28] demonstrated that this assumption is no longer valid for the small details in the landing gear, such as dressings, small details, rods, fixtures, etc.…”
Section: Correlation With Flow Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the noise levels generated by the LG system using wind-tunnel experiments [24,27,[31][32][33][34][35], aircraft flyover measurements [13,21,[36][37][38] and computational simulations [39][40][41][42]. Multi-approach studies [30,43] showed that all these three methods have their respective benefits and disadvantages, and that hybrid investigations combining two or more approaches can offer an improved solution.…”
Section: Introductionmentioning
confidence: 99%
“…These tones can be due to the landing gear bay itself [7,8], vortex shedding from cylindrical subcomponents of the landing gear, or resonances in the wheels cavities. The latter case is illustrated by the LAGOON experimental campaign led by Manoha et al in 2008 [9] who showed that two strong tones took place due to the excitation of the facing wheels cavities, and later by Bennett et al [10] on the ALLEGRA nose landing gear. This phenomenon has been thoroughly investigated with a dedicated LBM study by Casalino et al [11] in the case of the LAGOON geometry.…”
mentioning
confidence: 99%